2015
DOI: 10.1515/chem-2015-0128
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of activated carbons from biomass material – giant knotweed (Reynoutria sachalinensis)

Abstract: Activated carbons from biomass material of giant knotweed Reynoutria sachalinensis (F. Schmidt ex Maxim.) Nakai were obtained. Use of this plant for manufacturing activated carbon has not been studied yet. Therefore, the first activated carbons of giant knotweed origin are described. Both physicochemical (by steam and CO 2 ) and chemical (by KOH) activation methods were applied. Influences of temperature (500, 600, 700 and 800°C), burn-off [10, 25 and 50 wt. % (daf)] and KOH concentration on pores surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The KOH‐to‐char ratio is critical for obtaining biochar with high porosity and large pore size. A study by Fałtynowicz, Kaczmarczyk, and Kułazyński () observed a well‐developed porous texture of activated carbons when the KOH‐to‐char weight proportion was expanded from 2:1 to 3:1; however, the additional increment in the KOH‐to‐char proportion did not have a detectable effect. Therefore, the KOH‐to‐char ratio in this study was set at 3:1 for all the batches.…”
Section: Methodsmentioning
confidence: 99%
“…The KOH‐to‐char ratio is critical for obtaining biochar with high porosity and large pore size. A study by Fałtynowicz, Kaczmarczyk, and Kułazyński () observed a well‐developed porous texture of activated carbons when the KOH‐to‐char weight proportion was expanded from 2:1 to 3:1; however, the additional increment in the KOH‐to‐char proportion did not have a detectable effect. Therefore, the KOH‐to‐char ratio in this study was set at 3:1 for all the batches.…”
Section: Methodsmentioning
confidence: 99%
“…1). Biomass of this plant was investigated previously as feedstock for production of energy and activated carbons (Strašil and Kára 2010;Fałtynowicz et al 2015). This plant produces many secondary metabolites (Table 2) that are medically valuable, such as and phenylpropanoid glycosides.…”
Section: Giant Knotweed (Fallopia Sachalinensis Reynoutria Sachalinementioning
confidence: 99%
“…This observation is attributed to the intrinsic wider pore size characterized by G2, which allows efficient surface coating on the inner pore walls (Adelodun et al, 2015;Faltynowicz et al, 2015). This reduces the effect of blockage of narrower pores (supermicropores) which G1 is inherently susceptible to.…”
Section: Textural Characteristics Of Adsorbentsmentioning
confidence: 99%